Determinants of Low Birth Weight among Newborns Delivered at Public Hospitals in Sidama Zone, South Ethiopia: Unmatched Case-Control Study. (16th April 2020) - Bekela, Muse Bututa; Shimbre, Mulugeta Shegaze; Gebabo, Teshale Fikadu; Geta, Mengesha Boko; Tonga, Abayneh Tunje; Zeleke, Eshetu Andarge; Sidemo, Negussie Boti; Getnet, Agegnehu Bante
Abstract : Low birth weight is a global public health problem having various severe and life-threatening health effects. The World Health Organization is working to reduce the prevalence of low birth weight to 30% by the year 2025. Pinpointing the determinants of low birth weight at different scenarios is crucial to reduce the rate of low birth weight in low-income countries which consist of 96.5% of global low birth weight newborns. Thus, the aim of this study was to assess determinants of low birth weight in Sidama Zone public hospitals of South Ethiopia. An institution-based case-control study was conducted from March 1 to May 5, 2019, in Sidama Zone public hospitals. Data were collected from 354 mother-neonate samples with 118 of them having newborns with birth weight < 2500 g (cases) and 236 of them having birth weight ≥ 2500 g (controls) using a pretested, interviewer-administered structured questionnaire and medical record review. The odds of being rural dweller women was 3.51 times higher among cases (low birth weight babies) than among controls (normal birth weight babies) as compared to being urban dweller women (AOR = 3.51, 95% CI (1.91-6.45)). The likelihood of initiating antenatal care late was 3.22 times more among cases than among controls when compared with timely initiation of antenatal care (AOR = 3.22, 95% CI (1.47-7.14)). The probability of having pregnancy-induced hypertension was 4.49 times higher among mothers of the cases than among mothers of the controls as compared to not having pregnancy-induced hypertension (AOR = 4.49, 95% CI (1.94-10.38)). The odds of not taking iron and folic acid during pregnancy was 3.92 times higher among mothers of the cases than mothers of the controls when compared with taking iron and folic acid (AOR = 3.92, 95% CI (1.80-8.50)). The likelihood of having Mid-Upper Arm Circumference MUAC < 23 cm was 4.27 times higher among mothers of the cases than among mothers of the controls as compared to having MUAC ≥ 23 cm (AOR = 4.27, 95% CI (2.24-8.12)). The probability of having inadequate dietary diversity was 3.75 times higher among cases than among controls as compared to having adequate dietary diversity (AOR = 3.75, 95% CI (1.64-8.57)). Interventions targeting the aversion of low birth weight should focus on promotion of iron-folic acid supplementation and dietary diversification through timely initiation of antenatal care.